Secrets of Sufism in Iqbal’s Letter: Understanding and Analysis - Rizvi, Syed Tariq Hussain; Hussain, Tahir (sourcecoder, 2024)
This paper explores the mystical elements in Iqbal’s letters, particularly their role in understanding Sufi concepts of spiritual guidance and transformation. Letters serve as vital sources in biographical and personality studies, revealing the thoughts, beliefs, and emotional landscape of an individual. Iqbal’s letters offer invaluable insights into his personal spiritual journey and philosophical musings, especially in his later years when he had largely ceased reading other books, confining himself to the Quran and Rumi’s Masnavi for guidance. One letter, written to Hakim Muhammad Husain Arshi in 1935, stands out as a profound reflection on Sufi ideals, particularly the emphasis on shauq (spiritual longing) as an inner guide. Iqbal presents shauq not only as a driving force but as a mentor in itself, capable of transforming a seeker’s inner world and aligning them with divine love. Iqbal’s understanding of Sufism emphasizes the importance of a heartfelt connection with God, which cannot be achieved solely through intellectual pursuits. He critiques modern education systems for severing individuals from the cultural continuity and spiritual heritage that have long been essential for self-realization and moral development. In light of Iqbal’s philosophy, this paper analyzes the letter’s emphasis on nurturing spiritual enthusiasm (shauq) and the transformative power of association with enlightened individuals (suhbat). These concepts, which permeate Iqbal’s work, offer timeless guidance for personal development and social cohesion, advocating a life deeply rooted in spiritual warmth and unity with divine purpose.